THE ANALYTICAL HIERARCHY PROCESS (AHP) OF CONSUMER PURCHASE DECISION IN SELECTING BUBBLE TEA SHOP - Pangkey, Violita Flamy; Lapian, S.L.H.V Joyce; Tumewu, Ferdinand (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Bubble tea also known as pearl milk tea is a popular Taiwanese tea-based drink invented in Taichung in the 1980s. Nowadays bubble tea shops are really popping up all over the world. Bubble tea shops have mushroomed all around Indonesia over the last few years. In Manado, there are at least three bubble tea brands that are very popular in town, those are Share Tea, Cha Time and Tea Presso. In today’s era, the effect of the development of business has brought the business into a very tight competition to gain the attention of customers. In order to create a successful business, it is necessary to understand the factors that motivates consumers to make purchases. The purpose of this research are to identify which bubble tea shop that people in Manado prefer the most and to identify which criteria has major influence in selecting bubble tea shop. The method used in this research is Analytical Hierarchy Process (AHP). The main findings of this research are: 1) Based on the overall result that developed using Analytical Hierarchy Process (AHP), Share Tea become the most preferred bubble tea shop by the consumers with score 0.52, followed by Cha Time (0.29) and Tea Presso (019). 2) Among all the criteria, flavour became the major influence or the key consideration for consumers in selecting bubble tea shop. Keywords: consumer purchase decision, analytical hierarchy process